Intrauterine phenotypic features associated with 16p11.2 recurrent microdeletions. (30th March 2018) - Lin, Shaobin; Shi, Shanshan; Zhou, Yi; Ji, Yuanjun; Huang, Peizhi; Wu, Jianzhu; Chen, Baojiang; Luo, Yanmin
Abstract: Objective: To investigate the detection rate of 16p11.2 recurrent microdeletions in fetuses with abnormal ultrasound findings and determine the common abnormal ultrasound findings in fetuses carrying the deletion. Methods: This study reviewed 2262 consecutive fetuses with abnormal ultrasound findings who underwent prenatal chromosomal microarray analysis between October 2014 and December 2016. Cases carrying the 16p11.2 recurrent microdeletion were further genetically analyzed, and their clinical features were reviewed. Results: The 16p11.2 recurrent microdeletion was identified in 12 fetuses, who had skeletal malformations (5/12), cardiovascular malformations (4/12), or isolated ultrasound markers (3/12). Approximately 0.5% (12/2262) of the fetuses with abnormal ultrasound findings harbored the deletion. The 5 fetuses with skeletal malformations displayed vertebral defects, particularly in the hemivertebra and butterfly vertebra. The detection rate of the 16p11.2 recurrent microdeletion was statistically significant ( P  < .05) among fetuses with skeletal malformations (3.6%, 5/140), fetuses with cardiovascular malformations (1.1%, 4/367), and fetuses with isolated ultrasound markers (0.4%, 3/702). Conclusion: The most frequent ultrasound findings in fetuses with 16p11.2 recurrent microdeletions are skeletal malformations (particularly vertebral malformations), followed by cardiovascular malformations, and isolated ultrasound markers. Abstract : What's already known about this topic? The phenotypic features associated with 16p11.2 recurrent microdeletions have been well defined in postnatal cases. What does this study add? Our study indicates that the 16p11.2 recurrent microdeletion accounts for approximately 0.5% of fetuses with abnormal ultrasound findings, and the most frequent ultrasound findings may be skeletal malformations (particularly vertebral malformations), followed by cardiovascular malformations, and isolated ultrasound markers.